Simulation Analysis of Various Applications of a Combined Photovoltaic Panel with a Single-Channel Natural Flow Heat Collector - Asliddin Komilov (International Journal of Photoenergy)
The present article presents simulation results of a combined photovoltaic panel (PV) with natural flow single-channel thermal collector device (PV/T) for different thermal performance modes. The efficiencies of the PV/T and the same size photovoltaic panel are compared. Stress analysis was performed to realize the system’s limitation and resistibility to hydrostatic pressure. At different modes of operation, the photovoltaic efficiency was 6-15% higher for PV/T than for PV. The photovoltaic efficiency of PV/T was less influenced by insulation than that of PV, and combined thermal and photovoltaic efficiency was higher in insulated PV/T. Because of the hydrostatic pressure of water, the proposed design PV/T can use only limited existing PV panels which is a big disadvantage compared to other designs.